Multiaxial loading on a 3D woven carbon fiber reinforced plastic composite using tensile-torsion tests : Identification of the first damage envelope and associated damage mechanisms. (1st November 2019) - Tableau, Nicolas; Aboura, Zoheir; Khellil, Kamel; Laurin, Frederic; Schneider, Julien
Abstract: This study focuses on the experimental identification of the first damage envelope in a 3D woven composite with polymer matrix, under multi-axial loadings including combined in-plane tension and out-of-plane shear loadings (σ-τ envelopes). Proportional Tensile-Torsion tests on rectangular bars were performed to induce different multi-axial stress states. To enable envelopes identification, onset of the first damage has been evaluated thanks to the correlation of various and complementary investigation measurement techniques, such as Stereo-Digital Image Correlation (Stereo-DIC), Acoustic Emission (AE) and in-situ microscopic observations. In addition, a specific data reduction process has been used to manage accurate quantification of the stress state induced by the multi-axial loadings. Based on these findings, both σ11 -τ13 and σ22 -τ23 envelopes were identified on a 3D woven composite material with polymer matrix. Using microscopic observations, damage mechanisms (type and localization) related to the multi-axial loadings were identified. In addition, thanks to the strain fields measured by the Stereo-DIC on the material surface, particular relations between the multi-axial loadings and the 3D woven architecture have been established.